Sequence of antihypertensive medications used in preterm infants with hypertension: A cross-sectional study - Alejandro D. Perez; Mary-Carty Pittman; Kaniz Afroz Tanni; Keia R. Sanderson; Jieun Park; Daniel I. Feig; Matthew M. Laughon; Matthew Shane Loop (PLoS ONE, 2025)
Background Hypertension in preterm infants can result in life-threatening outcomes. However, there is limited evidence to guide the pharmacologic management of hypertension in preterm infants. Without population-level studies of the pharmacologic strategies that clinicians currently employ for hypertension in preterm infants, studies investigating the benefits and risks of these strategies cannot be performed. Methods A retrospective, cross-sectional study was conducted at a single academic medical centerto determine the most prevalent antihypertensive medication used for first-line, second-line, and adjunctive pharmacologic management among preterm infants with hypertension. The study sample included patients with a postnatal age less than 1 year at hospital discharge, gestational age at birth less than 37 weeks, and treated with an antihypertensive medication between July 2010 and December 2022. The prevalence of each antihypertensive medication used for each stage of pharmacologic management was estimated, and prevalences were compared using prevalence ratios. Bayesian multinomial regression was used to estimate prevalence ratios and 95% credible intervals (CIs). Results Out of 751 possibly eligible patient encounters obtained, 134 encounters were identified across 120 patients that met the inclusion criteria. Second-line and adjunctive pharmacologic management were used in 6 and 12 encounters, respectively. Propranolol had the highest prevalence for each stage of pharmacologic management: 61% for first-line (95% CI: 53-69%); 40% for second-line (95% CI: 14-70%); and 47% for adjunctive pharmacologic management (95% CI: 24-72%). As a first-line pharmacologic management, propranolol was 4.8 times (95% CI: 2.9-7.7) as prevalent as the second most prevalent medication (captopril). Conclusion In a large academic hospital, propranolol was the most commonly used medication for first-line antihypertensive pharmacologic management among preterm infants. The most prevalent medication used for second-line and adjunctive pharmacologic management was inconclusive.